Inokulasi Fungi Mikoriza Arbuskular Indigen Untuk Bibit Karet pada Tanah Bekas Tambang Batubara - Margarettha Margarettha (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Mining activities provide economic benefits and also cause environmental and land ecosystems damages. The damage caused by such top soil layer loss, drought, soil compaction, low water holding capacity, poor nutrient (macro nutrients), accumulation of toxic elements and highly acidic soil reaction. Mined land reclamation of coal with bio-fertilizer technology as arbuscular mycorrhizal fungi (AMF) indigenous is one of the technologies for revegetation of land with environmentally friendly systems. This study aims to get a AMF biofertilizers indigenous effective and adaptive for rubber seedlings planted in coal-mined soil. Research used a completely randomized design with one factor that the FMA indigenous derived from in coal-mined soil; A (without inoculation; B (inoculation of Glomus sp-5), C (inoculation of Glomus sp-6), D (inoculation of Glomus sp-7), E (inoculation of Glomus sp-12), F (inoculation of Glomus sp-15); G (inoculation Acaulospora sp-1), H (inoculation Acaulospora sp-2), I (inoculation Acaulospora sp-3), J (inoculation Acaulospora sp-4), K (a combination of all-Glomus sp), L (a combination of all Acaulospora sp), M (combined all-Glomus sp-sp and Acaulospora). Data were analyzed with a 5% level of variance followed by DMRT 5% level. parameters measured were AMF colonization, seedling height, dry weight, available P, pH and Al. Research results can be concluded that the inoculation of all AMF Glomus sp and Acaulospora sp gave the highest colonization 53.33%, increased soil pH 15%, decreased the Al 56% and increased the available P of 9.25%.